Report on the Observance of Standards and Codes, Accounting and Auditing : Module B - Institutional Framework for Corporate Financial Reporting, B.7 Audit Regulation, Quality Assurance, and Public Oversight - World Bank (World Bank, Washington, DC, 2017)
The purpose of this report is to gain an understanding of the regulatory environment for auditors in a jurisdiction and the extent of quality assurance and oversight that takes place. In the Report on the Observance of Standards and Codes (ROSC) Accounting and Auditing (A&A) diagnostic assessment, quality assurance (QA) refers to the system in place in a jurisdiction to monitor compliance of the work performed by independent auditors with applicable auditing, ethical, and other professional standards via on-site inspections and other activities. QA inspections and other activities may be carried out by a separate audit firm (a peer review system), a professional accountancy organization (which in some circumstances has been delegated this responsibility by a government body or regulator), or by an audit regulator independent of the accountancy profession. Questions are based on the core principles for independent audit regulators issued by the International Forum of International Audit Regulators (IFIAR) and statement of membership obligations, QA as issued by the International Federation of Accountants (IFAC). The report is structured as follows: regulatory environment for auditors; QA and audit oversight system; QA review procedures, approach, and communication of findings; QA inspectors; and investigations and sanctions.